Progressive Abduction Loading Therapy with Horizontal-Plane Viscous Resistance Targeting Weakness and Flexion Synergy to Treat Upper Limb Function in Chronic Hemiparetic Stroke: A Randomized Clinical Trial - Ellis, Michael D.; Carmona, Carolina; Drogos, Justin; Dewald, Julius P. A. (Frontiers in Neurology, 2018)
Background. Progressive abduction loading therapy has emerged as a promising exercise therapy in stroke rehabilitation to systematically target the loss of independent joint control (flexion synergy) in individuals with chronic moderate/severe upper extremity impairment. Pre-clinical investigations have identified abduction loading during reaching exercise as a key therapeutic factor to improve reaching function. An augmentative approach may be to additionally target weakness by incorporating resistance training to increase constitutive joint torques of reaching with the goal of improving reaching function by “overpowering” flexion synergy. The objective was therefore to determine the therapeutic effects of horizontal-plane viscous resistance in combination with progressive abduction loading therapy. Methods. 32 individuals with chronic hemiparetic stroke were randomly allocated to two groups. The two groups had equivalent baseline characteristics on all demographic and outcome metrics including age (59±11 years), time post-stroke (10.1±7.6 years), and motor impairment (Fugl-Meyer, 26.7±6.5 out of 66). Both groups received therapy 3 times/week for 8 weeks while the experimental group included additional horizontal-plane viscous resistance. Quantitative standardized progression of the intervention was achieved using a robotic device. The primary outcomes of reaching distance and velocity under maximum abduction loading and secondary outcomes of isometric strength and a clinical battery were measured at pre-, post-, and 3 months following therapy. Results. There was no difference between groups on any outcome measure. However, for combined-groups, there was a significant increase in reaching distance (13.2%, effect size; d=0.56) and velocity (13.6%, effect size; d=0.27) at post-testing that persisted for 3 months and also a significant increase in abduction, elbow extension, and external rotation strength at post-testing that did not persist 3 months. Similarly, the clinical battery demonstrated a significant improvement in participant-reported measures of “physical problems” and “overall recovery” across all participants. Conclusions. The strengthening approach of incorporating horizontal-plane viscous resistance did not enhance the reaching function improvements observed in both groups. Data does not support the postulation that one can be trained to “overpower” the flexion synergy with resistance training targeting constitutive joint torques of reaching. Instead, flexion synergy must be targeted with progressive abduction loading to improve reaching function. Trial Registration. ClinicalTrials.gov, NCT01548781.